Prevalence of helminthiasis and identification of worm species in buffaloes on smallholder farms in Jerowaru sub-district, East Lombok - Sriasih, Made; Depamede, Sulaiman N; Wariata, Wayan; Ali, Muhamad; Rosyidi, Anwar; Hasma, Hasma; Hadi, Imron (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Jerowaru sub-district is one of 21 sub-districts in East Lombok district. Many people raise buffaloes to fulfill their need for food of animal origin. However, the business is still hampered by diseases caused by worm infestation, which is economically detrimental. This study aimed to obtain data on the prevalence of helminthiasis in buffaloes and identify the types of worms that infest the animals. Fecal samples were collected from buffaloes kept in smallholder farms in several villages in the Jerowaru sub-district. Examination and identification of samples were conducted at the Microbiology and Biotechnology laboratory of the Faculty of Animal Science, University of Mataram, and the Banyumulek Animal Health laboratory. The results show that the prevalence of helminthiasis in buffaloes kept in smallholder farms in the Jerowaru subdistrict was 14.60%. The types of parasites infecting buffaloes consisted of Eimeria (13.48%) and Toxocara (1.12%). Although parasite infection intensity is categorized as mild, it is necessary to pay attention to the cleanliness of cattle pens, especially during the rainy season, so they are not wet and humid.